Pengaruh Corporate Governance Terhadap Financial disstres - Ayu Aditia Hariyani; Andi Kartika (Politeknik Ganesha Medan, 2021)
This study aims to examine and find empirical evidence regarding the influence of corporate governance as explained by managerial ownership, institutional ownership, independent commissioners, audit committee on financial distress in manufacturing companies listed on the IDX for the 2017-2019 period. In this study, leverage, profitability and company size are used as control variables. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The sample was selected using purposive sampling method and the results get a sample of 361 companies. The analytical tool used in this study is logistic regression. The test results show that managerial ownership has no effect on financial distress. Meanwhile, institutional ownership, independent commissioners, and audit committees have an effect on financial distress. Leverage and company size as control variables show results that are not in accordance with their function, namely that they do not affect financial distress, and profitability as control variables show results that are in accordance with their function and have an effect on financial distress